Incidencia de la cultura organizacional en el trabajo en equipo en el ministerio de inclusión económica y social [mies] distrito Latacunga en el año 2023” - Jácome Cayo, Katherin Fernanda (2023)
The present investigation had as main objective to determine the relationship between organizational culture and teamwork in the entity [MIES] of the city of Latacunga, where theoretical bases were established that helped to understand how organizational culture influences teamwork and that factors intervene in these processes, with the theoretical foundation, the current situation of the institution was briefly analyzed, where an instrument validated by experts in the institution was applied, considering that it is a public entity where the organizational culture and teamwork respond to models Established within the governmental guidelines, this instrument helped to collect the information that after its respective analysis allowed to determine the reality of the institution based on the variables described above and to carry out a discussion of the results.